Cardiac glycosides cause cytotoxicity in human macrophages and ameliorate white adipose tissue homeostasis. (3rd May 2021) - Olona, Antoni; Hateley, Charlotte; Guerrero, Ana; Ko, Jeong‐Hun; Johnson, Michael R.; Anand, Paras K.; Thomas, David; Gil, Jesus; Behmoaras, Jacques
Abstract : Background and Purpose: Cardiac glycosides inhibit Na + /K + ‐ATPase and are used to treat heart failure and arrhythmias. They can induce inflammasome activation and pyroptosis in macrophages, suggesting cytotoxicity, which remains to be elucidated in human tissues. Experimental Approach: To determine the cell‐type specificity of this cytotoxicity, we used human monocyte‐derived macrophages and non‐adherent peripheral blood cells from healthy donors, plus omental white adipose tissue, stromal vascular fraction‐derived pre‐adipocytes and adipocytes from obese patients undergoing bariatric surgery. All these cells/tissues were treated with nanomolar concentrations of ouabain (50, 100, 500 nM) to investigate the level of cytotoxicity and the mechanisms leading to cell death. In white adipose tissue, we investigated ouabain‐mediated cytotoxicity by measuring insulin sensitivity, adipose tissue function and extracellular matrix deposition ex vivo . Key Results: Ouabain induced cell death through pyroptosis and apoptosis, and was more effective in monocyte‐derived macrophages compared to non‐adherent peripheral blood mononuclear cell populations. This cytotoxicity is dependent on K + flux, as ouabain causes intracellular depletion of K + and accumulation of Na + and Ca 2+ . Consistently, the cell death caused by these ion imbalances can be rescued by addition of potassium chloride to human monocyte‐derived macrophages. Remarkably, when white adipose tissue explants from obese patients are cultured with nanomolar concentrations of ouabain, this causes depletion of macrophages, down‐regulation of type VI collagen levels and amelioration of insulin sensitivity ex vivo . Conclusion and Implications: The use of nanomolar concentration of cardiac glycosides could be an attractive therapeutic treatment for metabolic syndrome, characterized by pathogenic infiltration and activation of macrophages. LINKED ARTICLES: This article is part of a themed issue on Inflammation, Repair and Ageing. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.9/issuetoc